2023
DOI: 10.3389/fncel.2023.1181071
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal T cells function in the central nervous system homeostasis and neurodegenerative diseases

Abstract: Recently, a rising interest is given to neuroimmune communication in physiological and neuropathological conditions. Meningeal immunity is a complex immune environment housing different types of immune cells. Here, we focus on meningeal T cells, possibly the most explored aspect of neuro-immune cell interactions. Emerging data have shown that meningeal T cells play a crucial role in the pathogenesis of several neurodegenerative disorders, including multiple sclerosis, Alzheimer’s, Parkinson’s, and Huntington’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…In human MSA post-mortem tissue, we have previously reported an increase in CD8+ T cells within the putamen and substantia nigra[ 40 ]. Literature has also shown that CD8+ T cells are retained in dura and leptomeningeal spaces, and upon a stimulus in the brain, will infiltrate into the parenchyma and execute effector functions[ 1 ]. Our results potentially suggest a similar trafficking of CD8+ T cells into the brain that has been described in other studies as α-syn overexpression results in enhanced parenchymal CD8+ T cells but decreased dural CD8+ T cells ( Figure 1B and C ).…”
Section: Discussionmentioning
confidence: 99%
“…In human MSA post-mortem tissue, we have previously reported an increase in CD8+ T cells within the putamen and substantia nigra[ 40 ]. Literature has also shown that CD8+ T cells are retained in dura and leptomeningeal spaces, and upon a stimulus in the brain, will infiltrate into the parenchyma and execute effector functions[ 1 ]. Our results potentially suggest a similar trafficking of CD8+ T cells into the brain that has been described in other studies as α-syn overexpression results in enhanced parenchymal CD8+ T cells but decreased dural CD8+ T cells ( Figure 1B and C ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an important role of MLVs in the protection of the brain against pathogens and the development of neurodegenerative diseases [ 114 , 115 , 116 , 117 ]. Dysfunction of MLVs aggravates Aβ accumulation in the brain and significantly reduces the efficacy of immunotherapy against AD and brain tumors [ 43 , 44 , 118 , 119 ].…”
Section: Meningeal Lymphatics As a Target For Anti-amyloid Therapymentioning
confidence: 99%
“…This immune response activates immune cells, including macrophages and microglia, which discharge pro-inflammatory cytokines, chemokines, and other agents fostering inflammation and detriment to myelin and nerve cells. This inflammatory cascade can give rise to demyelinated plaques and axonal loss, the elongated projections of nerve cells accountable for transmitting electrical impulses [66,67].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Subsequently, the CNS endeavors to effect repair and remyelination, albeit often incomplete, potentially resulting in the formation of scar tissue (gliosis). The recurring cycles of inflammation, demyelination, and repair attempts contribute to the distinctive relapsing-remitting MS pattern, wherein symptoms exacerbate during relapses and partially alleviate during remissions [67].…”
Section: Multiple Sclerosismentioning
confidence: 99%